Links between tenure security and food security: Evidence from Ethiopia - Ghebru, Hosaena H.; Holden, Stein (International Food Policy Research Institute, 2013)
This study, thus, uses five rounds of household panel data from Tigray, Ethiopia, collected in the period 1998–2010 to assess the impacts of a land registration and certification program that aimed to strengthen tenure security and how it has contributed to increased food availability and thus food security in this food-deficit region.